Distinct cognitive changes in male patients with obstructive sleep apnoea without co-morbidities - Gnoni, Valentina; Mesquita, Michel; O'Regan, David; Delogu, Alessio; Chakalov, Ivan; Antal, Andrea; Young, Allan H.; Bucks, Romola S.; Jackson, Melinda L.; Rosenzweig, Ivana (Frontiers in Sleep, 2023)
Obstructive sleep apnoea (OSA) is a multisystem, debilitating, chronic disorder of breathing during sleep, resulting in a relatively consistent pattern of cognitive deficits. More recently, it has been argued that those cognitive deficits, especially in middle-aged patients, may be driven by cardiovascular and metabolic comorbidities, rather than by distinct OSA-processes, such as are for example ensuing nocturnal intermittent hypoxaemia, oxidative stress, neuroinflammation, and sleep fragmentation. Thus, we undertook to define cognitive performance in a group of 27 middle-aged male patients with untreated OSA, who had no concomitant comorbidities, compared with seven matched controls (AHI mean±S.D.:1.9±1.4 events/hr; mean age 34.0±9.3 years; mean BMI 23.8±2.3 kg/m2). Of the 27 patients, sixteen had mild OSA (AHI mean±S.D.:11.7±4.0 events/hr; mean age 42.6±8.2 years; mean BMI 26.7±4.1 kg/m2), and eleven severe OSA (AHI 41.8±20.7 events/hr; age: 46.9 ±10.9 years, BMI: 28.0±3.2 kg/m2). In our patient cohort, we demonstrate poorer executive-functioning, visuospatial memory, and deficits in vigilance sustained attention, psychomotor and impulse control. Remarkably, we also report, for the first time, effects on social cognition in this group of male, middle-aged OSA patients. Our findings suggest that distinct, OSA-driven processes may be sufficient for cognitive changes to occur as early as in middle age, in otherwise healthy individuals.